Endocardial fibroelastosis in infants with hydrops fetalis. - Newbould, M J (1991)
Endocardial fibroelastosis, defined as an endocardium in excess of 30 microns thick, was found in 10 out of 34 cases of hydrops fetalis in a review of 1589 perinatal necropsies carried out between 1976 and 1989. The infants comprised 16 cases of rhesus haemolytic disease, of whom three had endocardial fibroelastosis, and 18 cases of non-rhesus hydrops, of whom seven had endocardial fibroelastosis. Intrauterine congestive heart failure was thought to have been the probable cause of hydrops in eight of the 10 infants with endocardial fibroelastosis. None of an age matched control group without endocardial fibroelastosis had evidence of congestive cardiac failure. These observations support the hypothesis that endocardial fibroelastosis is an endocardial response to chronic prenatal myocardial stress.